Increased Dietary Inflammatory Index (DII) Is Associated With Increased Risk of Prostate Cancer in Jamaican Men - Shivappa, Nitin (Nutr Cancer, 2015)
PURPOSE: Prostate cancer is the most common non-skin malignancy; and it accounts for the most cancer deaths among Jamaican males. Diet has been implicated in the etiology of prostate cancer, including through its effects on inflammation. METHOD: We examined the association between a newly developed dietary inflammatory index (DII) and prostate cancer in a case-control study of 40-80 year-old Jamaican males. A total of 229 incident cases and 250 controls attended the same urology out-patient clinics at 2 major hospitals and private practitioners in the Kingston, Jamaica Metropolitan area between March 2005 and July 2007. The DII was computed based on dietary intake assessed using a previously validated food frequency questionnaire (FFQ) that was expanded to assess diet and cancer in this Jamaican population. Multivariable logistic regression was used to estimate odds ratios, with DII as continuous and expressed as quartiles. Logistic regression analysis adjusted for age, total energy intake, education, body mass index (BMI), smoking status, physical activity and family history of prostate cancer. RESULTS: Men in the highest quartile of the DII were at higher risk of prostate cancer [odds ratio (OR) = 2.39; 95% confidence interval (CI) =1.14–5.04 (P(trend) = 0.08)] compared to men in the lowest DII quartile. CONCLUSION: These data suggest a pro-inflammatory diet, as indicated by increasing DII score, may be a risk factor for prostate cancer in Jamaican men.